Type 1 Diabetes Mellitus and Thromboembolism in Pregnancy [A275]. (May 2022) - Thomas, Jacob; Brewerton, Charles; Holmgren, Calla; Harrison, Rachel
Abstract : INTRODUCTION: Type 1 diabetes mellitus (T1DM) is associated with vascular disease. The risk for thromboembolism in pregnancy is uncertain. We hypothesize that T1DM is associated with higher rates of thrombotic events in pregnancy. METHODS: This is a retrospective cohort study utilizing the National Inpatient Sample database from the Healthcare Cost and Utilization Project for all of 2018. Pregnant patients with a history of T1DM were compared to those without. The primary outcome was diagnosis of any thrombotic disease (pulmonary embolism [PE], deep vein thrombosis [DVT], cerebral vascular thrombosis [CVT], or other thromboses). Secondary outcomes included diagnosis of each individual type of thrombo-embolic event. Groups were compared via Student's test, Chi-square, and logistic regression analyses, controlling for confounders including age, race, obesity, tobacco use, chronic hypertension, asthma, anemia, and cesarean section. RESULTS: A total of 754, 721 subjects met criteria. Patients with T1DM encompassed 0.4% of subjects (N=3, 307). T1DM subjects were more likely to be younger, non-Hispanic White, obese, tobacco users, chronic hypertensive, and asthmatic and have a history of cesarean delivery ( P <.05 for all). They were less likely to be privately insured or in the top income quartile. Thromboembolic events occurred more frequently in those with T1DM (0.5% vs. 0.2%, P <.001). DVT was the most common event (0.3%). After controlling for confounders, T1DM remained associated with any thromboembolic event in pregnancy (adjusted odds ratio [aOR] 3.39, 95% CI 1.81–6.35), DVT (aOR 4.84, 95% CI 2.15–10.92), PE (aOR 4.87, 95% CI 1.19–19.88), and CVT (aOR 4.30, 95%CI 1.59–11.63). CONCLUSION: T1DM is associated with an increased risk of thrombo-embolic events in pregnancy.